2009
DOI: 10.1080/08870440701697367
|View full text |Cite
|
Sign up to set email alerts
|

The time course of attentional allocation while women high and low in body dissatisfaction view self and model physiques

Abstract: The purpose of this study was to examine trait levels of dissatisfaction with specific bodily regions and attentional characteristics associated with those regions among women high (HBD, n = 15) and low (LBD, n = 14) in body dissatisfaction. Separate laboratory visits were completed, during, which eye movements were recorded as participants viewed slides of self-physiques or model-physiques. Comparisons of search tendencies were made across the entire 5 s of slide presentation, and then within each of the ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
34
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 38 publications
6
34
2
Order By: Relevance
“…Attentional biases on eating, figure, or weight-related stimuli were demonstrated by several authors with various neuropsychological tests (10,11). This confirms the study result that individuals with an eating disorder view themselves as less attractive than other women (16). When it comes to their own body, however, they focus their attention much more on the ''unattractive'' body parts (13,15).…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…Attentional biases on eating, figure, or weight-related stimuli were demonstrated by several authors with various neuropsychological tests (10,11). This confirms the study result that individuals with an eating disorder view themselves as less attractive than other women (16). When it comes to their own body, however, they focus their attention much more on the ''unattractive'' body parts (13,15).…”
Section: Introductionsupporting
confidence: 74%
“…Janelle et al (16) once more compared study participants who are highly dissatisfied with their own body with study participants who are very satisfied with their own body and studied participants' behavior when these participants are looking at pictures of their own body and pictures of a thin, attractive model. They found that highly dissatisfied study participants had a different eye movement pattern than the controls: they first fixated on the pelvis region.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although they report differences in the fixation patterns between the women with AN and controls, there is only limited consensus on which areas are favoured or avoided 13, 14, 15, 16, 17, 18, 19. This may be due to methodological differences.…”
Section: Introductionmentioning
confidence: 97%